2015 American Control Conference (ACC) 2015
DOI: 10.1109/acc.2015.7172182
|View full text |Cite
|
Sign up to set email alerts
|

On multi-dimensional and noisy quadratic signaling games and affine equilibria

Abstract: Abstract-This study investigates extensions of the quadratic cheap talk and signaling game problem, which has been introduced in the economics literature. Two main contributions of this study are the extension of Crawford and Sobel's cheap talk formulation to multi-dimensional sources, and the extension to noisy channel setups as a signaling game problem. We show that, in the presence of misalignment, the quantized nature of all equilibrium policies holds for any scalar random source. It is shown that for mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Similar conclusions about the qualitative structure of Nash equilibria have since been derived in more general models of cheap talk, such as multidimensional sources [12], noisy channels [13], multiple senders [14], and hierarchical communication networks [15].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Similar conclusions about the qualitative structure of Nash equilibria have since been derived in more general models of cheap talk, such as multidimensional sources [12], noisy channels [13], multiple senders [14], and hierarchical communication networks [15].…”
Section: Introductionsupporting
confidence: 68%
“…Notice that the matrix E, which appears in the cost function of (13), has, at least, one negative eigenvalue. This is because multiplying a matrix from both sides by a symmetric and invertible matrix does not change the sign of its eigenvalues (see Sylvester's law of inertia [20, p. 282]).…”
Section: A Static Estimationmentioning
confidence: 99%
“…The problem of information extraction is related to the general problem of communication between sender and receiver with misaligned objectives studied in game theory [1,2,3] control theory [4,5,6], economics [7,8]. Our work is also related to the results in [9] where we discussed a case with a single sender and showed that the maximum rate of information extraction is bounded above by the Shannon capacity of a certain graph.…”
Section: Introductionmentioning
confidence: 89%
“…Thus, the main goal of this strand of works is to characterize the (Nash) equilibria of the induced game. Most of the existing work has focused on the static setting [16,8,50,3]. The work of [16] shows that when the state of the system (principal's private information) is one-dimensional and both the principals and the agents utilities are quadratic, the principals equilibrium strategy employs quantization.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The work of [16] shows that when the state of the system (principal's private information) is one-dimensional and both the principals and the agents utilities are quadratic, the principals equilibrium strategy employs quantization. More general models of cheap talk, such as multidimensional sources [8], noisy communication [50] and multiple principals with misaligned objectives [3], have been studied in the literature for static settings. There are a few works that study the dynamic version of the cheap talk communication [34,35].…”
Section: Review Of Related Workmentioning
confidence: 99%